Commonly Reported Problems and Coping Strategies During the COVID-19 Crisis: A Survey of Graduate and Professional Students - Wasil, Akash R.; Franzen, Rose E.; Gillespie, Sarah; Steinberg, Joshua S.; Malhotra, Tanvi; DeRubeis, Robert J. (Frontiers in Psychology, 2021)
Background: The COVID-19 crisis has introduced a variety of stressors, while simultaneously decreasing the availability of strategies to cope with stress. In this context, it could be useful to understand issues that people find most concerning and ways in which they cope with stress. In this study, we explored these questions with a sample of graduate and professional students. Method: Using open-ended assessments, we asked participants (n=305) to identify their biggest challenge or concern (“top problem”), their most effective way of handling stress (“effective strategy”), and their most common way of handling stress (“common strategy”). We applied thematic analysis and evaluated whether participants’ strategies corresponded with evidence-based practices (EBPs). Results: Participants frequently reported top problems relating to productivity (27% of sample), physical health (26%), and emotional health (14%). Distraction was the most frequently classified common strategy (43%), whereas behavioral activation was the most frequently identified effective strategy (50%). Participants who reported a common strategy classified as an EBP reported lower depressive and anxiety symptoms. In contrast, there was no evidence of an association between symptom levels and whether or not participants’ effective strategy was an EBP. Participants who reported the same strategy as both their common and effective strategy (29%) reported lower depressive symptoms than those whose common and effective strategies were different. Conclusions: Our findings highlight stressors that students are experiencing and ways they are coping during the COVID-19 crisis. We discuss how these findings can inform mental health promotion efforts and future research on coping with stressors.